2017
DOI: 10.1186/s12906-017-1844-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient benefit of dog-assisted interventions in health care: a systematic review

Abstract: BackgroundDogs are the most common companion animal, and therefore not surprisingly a popular choice for animal-assisted interventions. Dog-assisted interventions are increasingly used in healthcare. The aim of the review was to conduct a systematic literature review of quantitative studies on dog-assisted interventions in healthcare, with the intention of assessing the effects and cost-effectiveness of the interventions for different categories of patients.MethodsA systematic review of the scientific literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
83
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 52 publications
11
83
0
6
Order By: Relevance
“…This result is in line with other studies [1]. For example, Olsen, Pedersen [9] found significant effects of DAI on depression and QoL for nursing home participants with severe dementia.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result is in line with other studies [1]. For example, Olsen, Pedersen [9] found significant effects of DAI on depression and QoL for nursing home participants with severe dementia.…”
Section: Discussionsupporting
confidence: 92%
“…Commonly, DAI is prescribed for a certain indication by a professional such as an occupational therapist, a physiotherapist or a registered nurse [13]. However, despite growing knowledge within the research field, the evidence base is preliminary and rather weak [1,5], mainly because of small studies with small sample sizes that make it difficult to generalize the findings. The aim of the present study was to investigate the effects of DAIs on QoL in nursing home residents with moderate to severe dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…trained for social interaction with humans, such as dogs or horses) can participate. This therapy promotes the social interaction of individuals with dementia (Bernabei et al, ), reduces stress and pain in hospitalised patients (Bert et al, ) and is beneficial for the social skills of adults with mental health problems such as schizophrenia (Lundqvist, Carlsson, Sjödahl, Theodorsson, & Levin, ; Maujean, Pepping, & Kendall, ). Two meta‐analyses concluded that AAI improves social functioning and emotional well‐being in elderly people and in groups with a chronic health condition, anxiety or depression (Nimer & Lundahl, ; Virués‐Ortega, Pastor‐Barriuso, Castellote, Población, & de Pedro‐Cuesta, ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic literature review of Lundqvist et al 1 aimed to assess studies on dog-assisted interventions in healthcare and showed a great potential of dog-assisted therapy in treatment of psychiatric disorders. Psychiatry is one of the main indication fields of animal-assisted therapy 2.…”
Section: Introductionmentioning
confidence: 99%